PENGARUH PIJAT TERHADAP KUALITAS TIDUR BAYI USIA 3-6 BULAN DI KLINIK CAHAYA BUNDA - Mailiza Cahyani; Betty Prastuti (JOMIS (Journal of Midwifery Science), 2020)
Sleep is a top priority for babies, because this is when neuro brain repair occurs and approximately 75% of growth hormone is produced. One of the methods that can be used to fulfill your baby's sleep needs is with a massage. Babies who are massaged can sleep soundly, whereas when they wake up, their concentration will be fuller. In a preliminary study conducted on mothers who have infants aged 3-6 months stated that babies often wake up and cry every 1 to 2 hours of sleep, and babies are also less sleepy if the mother moves away from the baby. Research methods: quantitative analysis with quasy experiment research type. The population of this research is all infants aged 3-6 months who visit the maternal light clinic, amounting to 68 babies. The sampling technique used is total sampling. Data collection by doing massage, observation and questionnaire. The purpose of this research is to find out how effective massage is to sleep quality of babie, where with chi square statistical analysis with a degree of confidence 95% p = 0.05 obtained an effective massage to improve the quality of sleep of infants with (p = 0.003).So that it is good for Kilinik to apply baby massage as a routine care for babies and can be one of the standards of care that can provide the fulfillment of the need for security and comfort in babies.